Integration of the Paradigm of Inclusivity in the 21st Century Competency-Based PAI Curriculum Evaluation Model - Harun; Zidan Khalik (Al-Insan: Islamic and Humanities Perspectives Journal, 2025)
Educational developments in the era of globalization and digitalization have driven a paradigm shift in the education system, including Islamic Religious Education (IRE). Education in the 21st century is no longer limited to knowledge transfer but also functions as a means of character formation, skill enhancement, and the cultivation of universal human values aligned with 21st-century competencies. However, the current evaluation system of the IRE curriculum in many institutions remains cognitively oriented and has yet to fully integrate inclusivity and competence-based learning principles. This study aims to formulate a conceptual model for evaluating the IRE curriculum that integrates an inclusive paradigm with a 21st-century competency-based approach. The findings indicate that incorporating inclusivity into the IRE evaluation model aligns with Outcome-Based Education (OBE), which emphasizes contextual and holistic learning outcomes while fostering critical, collaborative, communicative, and creative skills. The proposed model highlights learning outcomes as key indicators, supported by differentiated rubrics and authentic assessments such as project-based and portfolio-based evaluations. It also introduces inclusive indicators such as accessibility, participation, and accommodation for students with special needs. Overall, this inclusivity-oriented model signifies an epistemological shift from content-based to outcomes-based evaluation, creating a humanistic, adaptive, and equitable framework for contemporary Islamic education